Using labview for measuring parameters and controlling torsion testing equipments - Le, Văn Cường; Tran, Huy Hùng (Journal of Technical Education Science, 2014)
This article focuses on the solution for measuring parameters and controlling a secondhand torsion testing equipment; This research has developed software and proposed electrical scheme to connect measurement equipments to computers and acquire signals from sensors mounted on the measurement equipments. The acquired electrical signals are processed and converted into physical values for evaluators such as twisting moment, angle of twist...and also controlling the equipment. In addition, the proposed solution is low-cost for controlling measurement equipments.